(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Our project presents an innovative web platform integrates cutting-edge Machine Learning (ML) technologies to revolutionize farming practices, equipping farmers with indispensable tools for precise crop and disease detection. Through image analysis and data-driven insights, our platform swiftly identifies crops, diagnoses diseases, and provides tailored fertilizer suggestions, optimizing productivity while minimizing resource usage. Acting as a direct conduit between farmers and consumers, our user-friendly full-stack application enables seamless direct sales, eliminating intermediary hurdles and establishing a transparent marketplace. This signifies a paradigm shift in agricultural cultivation, marketing, and consumption, empowering stakeholders and fostering efficiency and transparency.